Effect of chemically modified recycled carbon fiber composite on the mechanical properties of cementitious mortar. (15th September 2019) - Wang, Yan; Zhang, Shaohui; Luo, Daming; Shi, Xianming
Abstract: Proper chemical treatment of recycled carbon fiber composites (RCFC) has been demonstrated to potentially add value to them, by improving the performance of cementitious materials incorporating them. This laboratory investigation mainly explored the use of saturated (simulated concrete) pore solution (SPS) to treat RCFC that contains cured epoxy resin, before its use in cementitious mortar. A total of seven mortar mixtures were fabricated, incorporating untreated RCFC, RCFC treated by SPS for different time periods followed by triisopropanolamine (TIPA), or RCFC treated by montmorillonite nanoclay emulsion (mNCE, at the nanoclay dosage of 0.75% by weight of cementitious binder). The water-to-binder ( w/b ) ratio of all mortar mixtures was 0.50 and the RCFC was admixed at 1% by volume. The compressive strength and splitting tensile strength of RCFC reinforced mortar were evaluated. The chemical characterization (by FTIR), thermogravimetric analysis, and microscopic investigation (by SEM) helped explain the observed engineering performance data. The residue epoxy resin on the surface of the RCFC was removed by the immersion in SPS, but a long-time treatment may result in damage of the fiber surface. The chemical treatment of RCFC showed both mechanical and chemical benefits to its adhesion with the cementitious mortar. Admixing mNCE achieved outstanding strengths of the mortar similar to those of mortars treated by SPS for 0.5 h and then TIPA.